2010
DOI: 10.1128/mcb.00091-10
|View full text |Cite
|
Sign up to set email alerts
|

Differential Requirement for H2AX and 53BP1 in Organismal Development and Genome Maintenance in the Absence of Poly(ADP)ribosyl Polymerase 1

Abstract: Combined deficiencies of poly(ADP)ribosyl polymerase 1 (PARP1) and ataxia telangiectasia mutated (ATM) result in synthetic lethality and, in the mouse, early embryonic death. Here, we investigated the genetic requirements for this lethality via analysis of mice deficient for PARP1 and either of two ATM-regulated DNA damage response (DDR) factors: histone H2AX and 53BP1. We found that, like ATM, H2AX is essential for viability in a PARP1-deficient background. In contrast, deficiency for 53BP1 modestly exacerbat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 75 publications
2
29
0
Order By: Relevance
“…To maintain genome stability, this ATM-dependent alternative repair pathway along with ATMindependent HR may be required to properly repair DSBs, at least those arising in euchromatin. As PARP inhibition selectively kills cells defective for HR (16), it is consistent that H2AX Ϫ/Ϫ cells, which are defective for HR, are sensitive to PARP inhibitors, and combined PARP1 and H2AX deficiency causes embryonic lethality (45). In contrast, as loss of ATM does not impair HR, HR defects do not appear to be a contributing factor to the molecular mechanism of synthetic lethality imposed by combined loss of ATM and PARP1/2.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…To maintain genome stability, this ATM-dependent alternative repair pathway along with ATMindependent HR may be required to properly repair DSBs, at least those arising in euchromatin. As PARP inhibition selectively kills cells defective for HR (16), it is consistent that H2AX Ϫ/Ϫ cells, which are defective for HR, are sensitive to PARP inhibitors, and combined PARP1 and H2AX deficiency causes embryonic lethality (45). In contrast, as loss of ATM does not impair HR, HR defects do not appear to be a contributing factor to the molecular mechanism of synthetic lethality imposed by combined loss of ATM and PARP1/2.…”
Section: Discussionmentioning
confidence: 95%
“…Inhibitor Olaparib-ATM or H2AX deficiency in combination with PARP1 or PARP2 deficiency causes embryonic lethality (17,18,45). It is unclear whether ATM/H2AX deficiency contributes to this synthetic lethality through the same molecular mechanism.…”
Section: Loss Of Atm or H2ax Renders Cells Sensitive To The Parpmentioning
confidence: 99%
“…53BP1 also plays important roles in NHEJ (13,28,29). Although recently 53BP1 has been reported to be important for the choice between the NHEJ and homologous recombination (HR) repair pathways (30)(31)(32), previous studies demonstrated that 53BP1 is not required for HR (33) and IRIF for Rad51, a recombinase integral for HR (34,35). We therefore examined the effect of Rnf168 deficiency on DSB repair using reporter plasmids for NHEJ and HR (36)(37)(38).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, disabling NHEJ was shown to reverse the DNA-repair defects and chromosomal instability of FANCD2 mutants exposed to platinum cross-linking agents (11). Moreover, ablation of 53BP1, a molecule recently demonstrated to facilitate NHEJmediated DSB repair (38) in addition to its other roles (39), also rescued the genotoxicity of DNA-damaging agents in a BRCA1 background (34,40). These earlier studies provide support for a model in which unrestricted NHEJ could induce genomic instability and eventual lethality in HR-deficient cells.…”
Section: Discussionmentioning
confidence: 99%